2020
DOI: 10.1159/000509108
|View full text |Cite
|
Sign up to set email alerts
|

miR-325-3p Protects Neurons from Oxygen-Glucose Deprivation and Reoxygenation Injury via Inhibition of RIP3

Abstract: <b><i>Objective:</i></b> Recent reports have corroborated that micro­RNAs (miRs) are related to the pathological changes of cerebral ischemia-reperfusion (CIR) induced injury. This work aimed to unearth the role and potential mechanism of miR-325-3p in regulating neuronal survival in CIR injury. <b><i>Methods:</i></b> To conduct this investigation, we established an in vitro model of CIR injury by subjecting neurons to oxygen-glucose deprivation and reoxygenation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…JNK signaling is also an important contributor to chronic inflammatory pain, and may be continuously activated after nerve damage [ 24 ]. Importantly, previous studies have indicated that reducing RIP3-induced inflammation can meaningfully weaken JNK signaling; for instance, the inhibition of RIP3 by miR-325-3p was found to deactivate MAPK pathway members such as P38 and JNK, hence preserving neurons from damage due to oxygen-glucose deprivation/re-oxygenation [ 26 ]. While these findings revealed the relationship between RIP3 and JNK, it remained unclear whether RIP3-induced JNK signaling contributed to CCI-induced NP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…JNK signaling is also an important contributor to chronic inflammatory pain, and may be continuously activated after nerve damage [ 24 ]. Importantly, previous studies have indicated that reducing RIP3-induced inflammation can meaningfully weaken JNK signaling; for instance, the inhibition of RIP3 by miR-325-3p was found to deactivate MAPK pathway members such as P38 and JNK, hence preserving neurons from damage due to oxygen-glucose deprivation/re-oxygenation [ 26 ]. While these findings revealed the relationship between RIP3 and JNK, it remained unclear whether RIP3-induced JNK signaling contributed to CCI-induced NP.…”
Section: Resultsmentioning
confidence: 99%
“…C-Jun N-terminal kinase (JNK), a component of the MAPK signaling pathway, can be triggered by a variety of stress stimuli, and ultimately upregulates proinflammatory mediators that promote NP [ 25 ]. RIP3 has been reported to induce the JNK signaling pathway [ 26 ], but it is not clear whether this interaction contributes to NP.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs have been shown to play critical roles in many physiological and pathological processes including cancers and MIRI [25][26][27] and have been associated with MIRI, such as miR-24-3p and miR-325-3p. [28][29][30][31]…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been shown to play critical roles in many physiological and pathological processes including cancers and MIRI 25–27 and have been associated with MIRI, such as miR‐24‐3p and miR‐325‐3p 28–31 . Additionally, miR‐322 has been implicated in cardiomyocyte function as it is involved in the formation and specification of cardiomyocytes during development 32,33 .…”
Section: Discussionmentioning
confidence: 99%